(untitled) (Journal of the College of Basic Education, 2026)
This study aimed to design and standardize an integrated electronic system for measuring combined motor response speed and tactile precision of the arm in Paralympic fencing. It also aimed to determine the numerical values ​​for tests of combined motor response speed and tactile precision of the weapon-holding arm in Paralympic epee fencers, and to establish benchmarks for these tests. The researchers used a descriptive methodology. The study sample consisted of 65 advanced-level epee fencers from 16 clubs, including five participants for a pilot study, 30 for the development phase, and 30 for the standardization phase. The researchers found that the combined motor response speed and tactile precision tests yielded six standardized levels, which can be used to evaluate motor response time and tactile precision. The researchers recommend adopting these two tests as valid measurement tools for assessing combined motor response time and tactile precision in advanced-level Paralympic epee fencers.